Evolving Intersection Between Inherited Cancer Genetics and Therapeutic Clinical Trials in Prostate Cancer: A White Paper From the Germline Genetics Working Group of the Prostate Cancer Clinical Trials Consortium - Carlo, Maria I. (JCO Precis Oncol, 2018)
PURPOSE: Advances in germline genetics, and related therapeutic opportunities, present new opportunities and challenges in prostate cancer. The Prostate Cancer Clinical Trials Consortium Germline Genetics Working Group was established to address genetic testing for men with prostate cancer, especially those with advanced disease undergoing testing for treatment-related objectives and clinical trials. METHODS: The Prostate Cancer Clinical Trials Consortium Germline Genetics Working Group met monthly to discuss the current state of genetic testing of men with prostate cancer for therapeutic or clinical trial purposes. We assessed current institutional practices, developed a framework to address unique challenges in this population, and identified areas of future research. RESULTS: Genetic testing practices in men with prostate cancer vary across institutions; however, there were several areas of agreement. The group recognized the clinical benefits of expanding germline genetic testing, beyond cancer risk assessment, for the goal of treatment selection or clinical trial eligibility determination. Genetic testing for treatment selection should ensure patients receive appropriate pretest education and consent and occur under auspices of a research study whenever feasible. Providers offering genetic testing should be able to interpret results and recommend post-test genetic counseling for patients. When performing tumor (somatic) genomic profiling, providers should discuss the potential for uncovering germline mutations and recommend appropriate genetic counseling. In addition, family members may benefit from cascade testing and early cancer screening and prevention strategies. CONCLUSION: As germline genetic testing is incorporated into practice, further development is needed in establishing prompt testing for time-sensitive treatment decisions, integrating cascade testing for family, ensuring equitable access to testing, and elucidating the role of less-characterized germline DNA damage repair genes, individual gene-level biologic consequences, and treatment response prediction in advanced disease.